2022
DOI: 10.3390/ijms232113276
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram/Copper Suppresses Cancer Stem Cell Activity in Differentiated Thyroid Cancer Cells by Inhibiting BMI1 Expression

Abstract: Differentiated thyroid carcinomas (DTCs), which have papillary and follicular types, are common endocrine malignancies worldwide. Cancer stem cells (CSCs) are a particular type of cancer cells within bulk tumors involved in cancer initiation, drug resistance, and metastasis. Cells with high intracellular aldehyde hydrogenase (ALDH) activity are a population of CSCs in DTCs. Disulfiram (DSF), an ALDH inhibitor used for the treatment of alcoholism, reportedly targets CSCs in various cancers when combined with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…29,30 One of the main targets of the DSF/copper complex is the ubiquitin/proteasome system (UPS). 31 The ubiquitin/proteasome system is a highly regulated mechanism for intracellular protein degradation, which plays an essential role in many fundamental cellular activities. 32,33 A protein must be ubiquitinated before it can be transferred to the 26S proteasome system for degradation.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 One of the main targets of the DSF/copper complex is the ubiquitin/proteasome system (UPS). 31 The ubiquitin/proteasome system is a highly regulated mechanism for intracellular protein degradation, which plays an essential role in many fundamental cellular activities. 32,33 A protein must be ubiquitinated before it can be transferred to the 26S proteasome system for degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Cells with high intracellular aldehyde hydrogenase (ALDH) activity are the population of CSCs in DTCs. Yung-Lun Ni et al found that DSF/copper can target the B lymphoma Mo-MLV insertion region 1 homolog (BMI1) by inhibiting c-Myc or the E2F1-mediated expression of CSCs in DTCs [ 96 ]. Therefore, DSF/copper is a potential therapeutic agent for the future treatment of DTCs.…”
Section: Application Of Novel Copper Complexes In Tumor Therapymentioning
confidence: 99%
“…In another approach, Yung-Lun Ni et al reported that disulfiram, an approved drug for the treatment of alcoholism, targeted cancer stem cells in thyroid carcinoma when combined with copper [8]. Indeed, the combination of disulfiram and copper not only hindered cell proliferation but also suppressed spheroid formation and inhibited the activity of cancer stem cells in multiple differentiated thyroid carcinoma cell lines.…”
mentioning
confidence: 99%